Body weight concerns: Cross-national study and identification of factors related to eating disorders - Da Silva, Wanderson Roberto [UNESP]; Santana, Moema De Souza [UNESP]; Maroco, João; Maloa, Benvindo Felismino Samuel; Campos, Juliana Alvares Duarte Bonini [UNESP] (Public Library of Science (PLoS), 2017)
Background: Body weight concerns are common among individuals with eating disorders, and this construct can be assessed using psychometric instruments. The Weight Concerns Scale (WCS) is commonly used to assess body weight concerns. Aims: To evaluate the psychometric properties of the WCS with Brazilian, Portuguese, and Mozambican female college students; to estimate body weight concerns; and to identify factors related to eating disorders. Methods: Confirmatory factor analysis was performed. Factorial, convergent, concurrent, and divergent validity, as well as reliability, were assessed. Cross-national invariance was tested by means of multigroup analysis. Structural models were tested using the WCS as the dependent variable, while demographic and academic variables and body mass index were used as independent variables. Logistic models were tested to estimate the likelihood of eating disorders being developed in specific groups. Results: Participants were 2,068 female students. The psychometric properties of the WCS were adequate for the Portuguese sample; however, for the Brazilian and Mozambican samples, it was necessary to correlate the errors of two items to improve model fit. The WCS did not show cross-national invariance. The variables “thoughts about dropping out of college,” “medication use because of studies,” “medication and supplements use for body change,” “body mass index,” “socioeconomic status,” “age,” and “performance in course” were significant predictors of body weight concerns. Overall, 24.4% (95% confidence interval = 22.9–26.7) of the students were likely to develop eating disorders. Students under 21 years old, who use medication and supplements for body change, and who were classified as overweight/obese have increased likelihood of developing eating disorders. Conclusion: The WCS showed good psychometric properties with Brazilian, Portuguese, and Mozambican students; however, it did not show cross-national invariance. We identified important aspects for investigating body weight concerns and factors related to eating disorders.